Cyber security : essential principles to secure your organisation - Calder, Alan, 1957- (IT Governance Publishing, 2020)
"Cyber Security: Essential principles to secure your organisation takes you through the fundamentals of cyber security, the principles that underpin it, vulnerabilities and threats, and how to defend against attacks"-- Provided by publisher.
Keywords: Computer security.; elektronické knihy; electronic books